Acoustic radiation performance manipulation of metamaterials based on uneven-depth grooves. (12th November 2019) - Zhang, Xiaowei; Lan, Jun; Liu, Xiaozhou
Abstract: In this paper, the plane wave expansion model is introduced to analyze the effect of a metamaterial with an uneven groove depth distribution on the radiation performance of a sound source, such as on directivity and transmission efficiency. The optimal groove depth distributions for two applications that need to maximize and minimize the transmission efficiency are obtained on the basis of this method. Further, the proposed plane wave expansion model can be degenerated to the acoustic grating model and the effective medium model with certain constraints.